Fostering entrepreneurship in Azerbaijan - Kuriakose, Smita (Directions in Development, 2013)
Job creation and productivity growth are at the forefront of the global development agenda. This is particularly relevant for Azerbaijan, whose government faces a central challenge to create conditions that will facilitate growth in nonoil tradable sectors. This study seeks to identify determinants of high-growth entrepreneurial activity. The study uses data from the new 2012 World Bank Entrepreneurship Survey conducted to gauge new firm growth in the formal sector in Azerbaijan and data from World Bank Enterprise Surveys to analyze innovative activity in existing firms. It includes detailed case study analyses to complement these findings. The study finds that high-growth entrepreneurialism is low in Azerbaijan and that innovative activity among firms is very low. Several factors hinder business growth and entrepreneurship. These include a lack of competition, financial systems that are not conducive to business development and a lack of industry-relevant skills. While outlining broad policy directions in areas namely improving competition and access to information, improving the business environment, increasing access to finance, developing skills, increasing access to markets, incentivizing greater in-firm research and development and raising awareness it lays out some priority areas that the government could embark on. The government could remove bottlenecks that impede entrepreneurialism in the general business environment and design new financial policy instruments to foster entrepreneurship and innovation. We hope that the issues discussed and the dialogue initiated during the course of this study would lend itself to policy design to foster high-growth entrepreneurship with a view to higher growth and job creation in this highly globalized world.